2019
DOI: 10.1002/mma.5889
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation analysis for a fractional‐order chemotherapy model with two different delays

Abstract: Cancer is one of the most serious diseases in the world. The investigation on cancer treatment has attracted great attention from medical workers, mathematical researchers, and scholars in various fields. To understand the intrinsic characteristics of cancer, numerous scholars have established cancer treatment models and discussed the dynamical properties. However, the main work of many scholars only focuses on the integer-order cancer treatment models, while the study on fractional-order ones is quite a few. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…In view of Lemma 3.7 of [45], we have the following conclusions. For the proof of this lemma, one can see [45]. Here we omit it.…”
Section: Bifurcation For System (2) With ϑ 1 = �mentioning
confidence: 68%
“…In view of Lemma 3.7 of [45], we have the following conclusions. For the proof of this lemma, one can see [45]. Here we omit it.…”
Section: Bifurcation For System (2) With ϑ 1 = �mentioning
confidence: 68%
“…In addition, it is worth mentioning that the protein synthesis process takes a certain time, so the time delay in the gene expression process is ubiquitous and inevitable. Theoretically, time delay usually leads to the system oscillations [34–36]. Specifically, the process from the transcription factor acting on the gene promoter to the appearance of mature mRNA often takes an average of about 10–20 min [37].…”
Section: Model Formulationmentioning
confidence: 99%
“…Moreover, time delays also affect the evolution and survival of cancerous cells in the presence of immune cells and host cells [33]. The impact of chemo-drug delivery delays on cancer and normal cells has been explored in [34]. Das et al [35] reported that uniform activation of helper T cells may stimulate effector cells and reduce tumor density.…”
Section: Introductionmentioning
confidence: 99%